Individual fMRI maps of all phalanges and digit bases of all fingers in human primary somatosensory cortex - Schweisfurth, Meike A.; Frahm, Jens; Schweizer, Renate (Frontiers in Human Neuroscience, 2014)
This study determined the individual maps of all fingers in BA 3b of the human primary somatosensory cortex in a single fMRI session by tactile stimulation at 19 sites across all phalanges and digit bases of the 5 right-hand digits. To quantify basic features of the digit maps within and across subjects, we applied standard descriptive measures, but also implemented a novel quantitative analysis. This so-called Direction/Order (DiOr) method tested whether subjects exhibited an ordering of peak fMRI representations along their individual direction of alignment through the set of analyzed phalanges and whether these individual directions were similar across subjects. Across-digit analysis demonstrated that for each set of homologous phalanges, the D5-to-D1 representations were successively represented along a common direction of alignment. Hence, the well-known mediolateral D5-to-D1 somatotopy was not only confirmed for the distal phalanges (p1), but could also be shown for the medial (p2) and proximal phalanges (p3). In contrast, the peak activation for the digit bases (p4) only partly elicited that digit succession. Complementary, intra-digit analysis revealed a divergent picture of map topography for the different digits. Within D5 (and in a trend: D4), an ordered p1-to-p3 succession was found across subjects, pointing to a consistent intra-digit somatotopy for D5, with p3 generally found medial-posterior to p1. In contrast, for D1, D2, and D3, most subjects did not present with ordered p1-to-p3 maps nor were directions of alignment similarly oriented between subjects. These digits therefore exhibited highly diverse representation patterns across subjects.